1979
DOI: 10.1079/wps19790008
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Fertility Potential of Broiler Breeder Males

Abstract: Semen Quality Characteristics and FertilityThe selection of males for breeder flocks is usually based on such characteristics as posture, body conformation, maturity, body size, ~~~~ ~ ~ ~ *Ha. Agr. Exp. Sta. Journal Series No. 1062. 95 96condition of the legs and feet, appearance of the head, general health and vigour, and appearance of eyes. Although these characteristics are useful in selecting males they do not assure that high fertility will be obtained. Several attempts have been made to relate various s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
1
5

Year Published

1981
1981
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(31 citation statements)
references
References 83 publications
2
23
1
5
Order By: Relevance
“…The correlation between motility and fertilizing capacity of poultry semen has generally been reported to be poor (Lake, 1962 ;Wilson et al, 1979) and this generalization was confirmed in the present study. For example, the addition of DMSO reduced motility immediately by 5 to 15 p. 100 but had no effect on fertility (tables 1 and 2).…”
supporting
confidence: 80%
“…The correlation between motility and fertilizing capacity of poultry semen has generally been reported to be poor (Lake, 1962 ;Wilson et al, 1979) and this generalization was confirmed in the present study. For example, the addition of DMSO reduced motility immediately by 5 to 15 p. 100 but had no effect on fertility (tables 1 and 2).…”
supporting
confidence: 80%
“…Já em outros trabalhos, comparando galos com 35 e 68 semanas de idade, Rocha Júnior e Baião (2001) concluíram que não houve diferença nas características espermáticas entre as idades. Nos galos, a redução na fertilidade está associada a redução no número de espermatozóides no ejaculado e na redução do volume de sêmen produzido (LAKE, 1989), apresentam também libido diminuída e menor número de cópulas férteis (WILSON et al, 1979). Nas codornas analisadas não foram avaliados os parâmetros seminais dos machos, porém, o numero de espermatozóides fornece uma visão indireta da quantidade de espermatozóides que as fêmeas receberam naquele período.…”
Section: Discussionunclassified
“…Considerando que os machos tiveram o mesmo manejo sanitário e nutricional, não era esperado efeito deste trabalho sobre a fertilidade dos ovos, ANSAH et al (1977), WILSON et al (1979), HARRIS et al (1984), WILSON et al (1987), HOCKING (1989), HOCKING e DUFF (1989).…”
Section: -Coeficiente De Variação (Coefficient Of Variation)unclassified